DELAYED BLEEDING IN ANTICOAGULATED PATIENTS AFTER BLUNT HEAD TRAUMA. Issue 12 (23rd November 2015) - Kuczawski, M; Mason, S; Teare, M; Stevenson, M; Goodacre, S; Holmes, M; Harper, R; Ramlakhan, S; Morris, F
Abstract : Objectives & Background: The AHEAD Study aimed to determine the head injury complication rate and identify risk factors associated with a poor outcome in patients taking warfarin after blunt head trauma. The presence of neurological symptoms was associated with an increased risk of adverse outcome. As delayed bleeding is of concern in this cohort of patients, we undertook exploratory analyses of those patients who re-attended the emergency department (ED) after discharge. Methods: The study was undertaken in 33 type I EDs from October 2011 for 18-months. 3, 566 adult patients taking warfarin with blunt head trauma were enrolled into the study. Anonymised patient-level data including time to CT head scan and details of any re-attendance to the ED within 10 weeks of the original episode were collected and available for 3534 patients. We examined the presentation and outcomes of those patients re-attending the ED with a related attendance. Results: Of the 3534 patients in the study, 557 re-attended the ED of which 98 patients (2.8%) presented with a head-injury related condition, and 37 (1.1%) patients re-attended with a reason related to the original head-injury. In this patient group (median age 75.8 years; mean INR 2.59 (SD 0.82); GCS=15 86.5%): 0.54% (n=19) did not present with any neurological symptoms; 0.6% (n=21) were admitted and 0.48% (n=17) underwent CT scanning, 73.3% (n=11) of which were within 4 hours of attendance. There were significant head injury-related CT findings in 0.08% (n=3) patients; no patients underwent a neurosurgical procedure. Median number of days to re-attendance was 3 days (range 0–46 days) with length of re-attendance stay median 2 days (range 0–44 days). Neurosurgery was performed on 0.06% (n=2) patients that re-attended and 0.14% (n=5) patients died; 2 deaths were head-injury related but both patients originally presented with no symptoms and GCS=15, no CT scans were performed and the patients were not admitted. Conclusion: Only a small fraction (1.1%) of anticoagulated patients re-attended the ED after discharge from their original ED attendance for blunt head trauma. On re-attendance, 2 (0.06%) patients died due to head-injury related reasons however on their original presentation to the ED, both patients were neurologically normal. The rate of delayed complications is very low following head injury in patients on warfarin and there is no justification for admission and prolonged observation of these patients.